TEACHING VOCABULARY THROUGH THINK PAIR SHARE TO THE SEVENTH GRADE STUDENTS AT SMP NEGERI 3 CIMAHI - Aulia Rahma Putri; Iman Santoso (IKIP Siliwangi, 2021)
There are two objectives of this study. The first is to observe the students’ perception on teaching english vocabulary through Cooperative Learning, and the next objective is to know students’s ability in mastering vocabularies. The method which used by the researcher is Classroom Action Research with the technique is Think Pair Share (TPS). The objective of this research is also to identify the benefits that the students obtained from that technique. The respondents of the research were seventh grade students of SMP Negeri 3 Cimahi in the school year of 2018/2019. In this research, the researcher implemented the research on two cycles for seven meetings. Each cycle consist four steps. They are planning, acting, observing, and reflecting. In the first cycle, there are four meetings. In first meeting, the researcher gave the pre-test to the students. That is for knowing the student’s ability in the first. Next meeting, the researcher do the first treatment, and second treatment was done in third meeting. So, in the last meeting of cycle 1, the researcher gave the post-test to the students. While, those are three meetings in cycle 2. In the first meeting, the researcher gave the third treatment. This is for continuing the treatment in cycle 1. After that, in the second meeting, the researcher gave the fourth treatment. So, in the last meeting of cycle 2, the researcher gave the post test for the students. The results of the study that the teaching english vocabulary through Think Pair Share (TPS) technique could help students’ vocabulary in learning english because they can share the knowledge about English, especially in vocabularies with the other friends. And this technique also can make the enjoyable learning in activity learning in the classroom. Keywords: Vocabulary, Think Pair Share (TPS), Cooperative Learning